Nature versus Nurture in Social Mobility Under Private and Public Education Systems. (January 2023) - Fan, Simon; Pang, Yu; Pestieau, Pierre
This paper analyzes the roles of innate talent versus family background in shaping intergenerational mobility and social welfare under different education systems. We establish an overlapping-generations model in which the allocation of workforce between a high-paying skilled labor sector and a low-paying unskilled labor sector depends on talent, parental human capital, and educational resources, and the wage rate of skilled workers is governed by their average talent. Our model suggests that under the private education system, income inequality is inversely associated with social mobility, and the steady-state average talent of skilled labor declines as parents increase educational spending. The introduction of public education, which makes the allocation of workforce depend more on talent and less on family background, tends to increase both inequality and mobility and improve welfare under reasonable conditions. Our simulations show that if the government diverts public school funding to redistribution, the economy has lower inequality and mobility in the steady state. Moving from elitist to meritocratic systems yields lower inequality and greater mobility.